In vitro morphogenesis in zygotic embryo cultures of carob tree (Ceratonia siliqua L.) - Custódio, Luísa (2015)
In this study, organogenic cultures were induced from zygotic embryos of carob tree. Basal medium consisted of Murashige & Tucker (1969), supplemented with 0.5 or 1 mg L-1 of 2,4-dichlorophenoxyacetic acid alone or combined with 0.5, 1, 2, 3 and 4 mg L-1 of kinetin. Calli initiation occurred in all the hormonal combinations tested. The zygotic embryo cultures differentiated two types of regenerants: somatic embryos (SEs) and shoots, with a maximum frequency of 30 and 100%, respectively. SEs exhibited morphological abnormalities, such as fusion and absence of cotyledons, and showed secondary embryogenesis. The regenerated shoots were rooted, hardened and transferred to the soil.